2016
DOI: 10.1177/1526602816636891
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Patient-Level Meta-analysis of the Streamliner Multilayer Flow Modulator in the Management of Complex Thoracoabdominal Aortic Pathology

Abstract: The SMFM can be safely utilized in some patients with complex thoracoabdominal pathologies provided operators adhere to the IFU. The SMFM is a novel technology with no long-term published data on its sustained effectiveness and a lack of comparative studies. Randomized clinical trials, registries, and continued assessment are essential before this flow-modulating technology can be widely disseminated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 34 publications
3
50
0
Order By: Relevance
“…Hynes and colleagues reported a systematic review of 15 publications including 171 patients treated for TAAAs with mean age of 69 years. 35 Technical success was 77%, and there were no cases of spinal cord injury. Aneurysm-related survival at 1 year was 78%, and allcause survival was only 50%.…”
Section: Clinical Evidencementioning
confidence: 93%
See 2 more Smart Citations
“…Hynes and colleagues reported a systematic review of 15 publications including 171 patients treated for TAAAs with mean age of 69 years. 35 Technical success was 77%, and there were no cases of spinal cord injury. Aneurysm-related survival at 1 year was 78%, and allcause survival was only 50%.…”
Section: Clinical Evidencementioning
confidence: 93%
“…In the study of Sultan and colleagues, important limitations were the retrospective design, short follow-up interval (w1 year), and the large number of patients (38%) who were lost to follow-up in the initial Global Registry cohort. 35 Although MFM stents promote aneurysm and false lumen thrombosis, several reports and one meta-analysis have shown continued aortic enlargement in treated segments. 27,28,33,34 Overall, there is lack of evidence that MFM stents effectively prevent aneurysm rupture and aortic-related deaths beyond 1 year of follow-up.…”
Section: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…These include device foreshortening resulting in inadequate overlap of devices or device dislocation, poor SMFM sizing often undersizing, and inadequate overlap between devices or device foreshortening, which can result in failure mode I or between two overlapping stents, resulting in failure mode II. 39 The authors postulate that treatment of CSAD with the SMFM equalize arterial pressure between the true and false lumen. This thereby stabilizes the injured aortic wall, and reduces aneurysm formation as it covers normal-to-normal aorta without compromising the side branches.…”
Section: Reintervenɵon Free Survivalmentioning
confidence: 99%
“…In 2016, Hynes et al. [2] published a meta-analysis of MFMS reviewing data on 171 patients with complex aortic pathology (59.1% had TAAA). They found that the aneurysm-related survival rate was 78.7% at 1 year and 66.6% at 18 months.…”
Section: Discussionmentioning
confidence: 99%